Introduction of CME Credit System amongst Doctors of Bangladesh Armed Forces (Journal of Armed Forces Medical College, Bangladesh, 2024)
Abstract not availableJAFMC Bangladesh. Vol 19, No 1 (June) 2023: 1-5